2019
DOI: 10.1159/000499072
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Thalamic Stimulation Induced Relapsing Encephalitis

Abstract: Deep brain stimulation of the anterior thalamic nucleus is one of the promising therapeutic options for epilepsy. Several studies are still under way to further strengthen and clarify the mechanism, efficacy, and complications. Contrary to hardware-related and operation-related events, the stimulation-related adverse effect is mild, target-dependent, and adjustable. We present a case of relapsing herpes simplex encephalitis (HSE) as a newly reported and potentially fatal stimulation-related adverse effect foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…There is evidence that deep brain stimulation of the anterior and centromedian nuclei of the thalamus, subthalamic nucleus, striatum, globus pallidus and cerebellum are effective in controlling seizures [158][159][160][161]. There is one study in which stimulation of the anterior thalamic nucleus inhibited SE in experimental pilocarpine rat models [161], but the use of deep brain stimulation in the treatment of SRSE in humans is underwhelming.…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…There is evidence that deep brain stimulation of the anterior and centromedian nuclei of the thalamus, subthalamic nucleus, striatum, globus pallidus and cerebellum are effective in controlling seizures [158][159][160][161]. There is one study in which stimulation of the anterior thalamic nucleus inhibited SE in experimental pilocarpine rat models [161], but the use of deep brain stimulation in the treatment of SRSE in humans is underwhelming.…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…ANT-DBS is generally safe and well tolerated, but several adverse events are associated with it, either hardware-related or operation-related complications, which mostly occur around the time of device implantation 3 . While the stimulation-related adverse effect is usually mild and adjustable, a recent report presented a unique case of herpes simplex encephalitis reactivation 1 month after ANT-DBS implantation among patients with DRE, providing evidence for a role of ANT-DBS in the modulation of the inflammatory response 7 .…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that virologic relapse in HSE is a consequence of reactivation of a latent HSV in the trigeminal or olfactory root ganglia whereas first HSE episodes follow viral ascent from oral sites via the trigeminal or olfactory nerves in HSV-1 and from genital sites via sacral nerve roots in HSV-2 [5]. It has been observed that reactivation of latent HSV infection leading to virologic relapse of HSE may follow immunosuppression [13], chemoradiation [14], and deep brain stimulation among others [15].…”
Section: Introductionmentioning
confidence: 99%